Análise da construção e implementação de uma atividade de educação interprofissional na saúde do trabalhador - Griggio, Ana Paula (2019)
Based on the theoretical references of Interprofessional Education and Collaborative Practice and on work as a Social Determinant of Health, this study aimed to analyze the construction and implementation of an Interprofessional Education Activity (AEIP) focused on Occupational Health. It was a Research-Action which comprised two steps: (1) planning and (2) implementation and evaluation of the activity, developed at a Higher Education Institution. The planning step was performed in five workshops and had the participation of six professors, who were two physiotherapists, a physical educator and three nurses, and a nursing undergraduate student. The implementation and evaluation step happened in 15 meetings, adding up to 60 hours, with the participation of 16 people, who were five undergraduate students, three graduation students, five professors and three health network professionals, representatives of Nursing, Physical Education, Physiotherapy, Gerontology and Psychology areas. In both steps, the data were collected through registers in field journal and compiled in synthesis in the planning step and analyzed by Thematic Analysis in the implementation of the activity. The evaluation was performed processually, throughout the meetings, and, in the end, through an evaluative form, built exclusively to this end, analyzed through simple descriptive statistics and synthesis of textual answers. The workshops in the planning step made possible the construction of three professional competences: (1) Integrality of care; (2) Work as social determinant of the health-sickness process and (3) Work in interprofessional team. It resulted in a consistent activity, conceived by multiple views, experiences, knowledges and perspectives, which would not obtain such richness if it was planned isolatedly, by a single professional group. The AEIP implementation resulted in three thematic categories aligned with the competences built in the previous step. In the AEIP evaluation, the participants pointed out satisfaction with the activity, highlighting the importance of the proposal and the opportunity to discuss the topics with different professionals, experiences and perspectives, encouraging new AEIP offers. The field journal registers demonstrate that Occupational Health is still a gap in the health professionals training curriculum, which lacks investments, and that Interprofessional Education is a qualifying strategy in health professionals training, able to result in significant changes in the way to produce care and health.